Neuroprotective Effect of Porelis, A Standardized Extract of Purple Tea (Camellia sinensis) Comprised of GHG in a 6-OHDA Induced Cellular Model of Parkinson’s Disease - Gouthamchandra, Kuluvar; Venkataramana, Sudeep Heggar; Ranganath, Bhoomika; Amritharaj, Amritharaj; Basavegowda, Lingaraju Harakanahalli; Parameshwarappa, Prasanna Kumara Thammatadhalli; Kodimule, Shyam Prasad (Indian Journal of Pharmaceutical Education and Research, 2025)
Introduction: Camellia sinensis is the most frequent used plant source for making tea, which are categorized as green, white, yellow, oolong, black and dark, among them, purple tea is a new variant of green tea developed in Kenya, it is believed that purple tea has greater health advantages than green tea because of its unique composition, which includes significant concentrations of anthocyanins and anthocyanidins. Objectives: This study aimed to evaluate the protective effect of Porelis, a standardized purple tea extract against oxidative stress and apoptosis caused by 6-Hydroxydopamine (6-OHDA). Materials and Methods: To evaluate the vitality of the cells, the MTT test was employed, to create an in vitro Parkinson's disease model, SH-SY5Y cells were treated with 60 µM of 6-OHDA for 24 hr. The levels of antioxidant enzymes, anti-inflammatory mediators and apoptotic markers were evaluated using western blotting. Results: The Porelis pretreatment significantly increased the cell viability of damaged SHSY-5Y cells stimulated with 6-OHDA and restored the levels of antioxidant enzymes including Superoxide Dismutase (SOD) and Catalase (CAT). The Porelis effectively lowered 6-OHDA-induced neuroinflammation by subsiding the expression levels of COX-2 and iNOS. Additionally, via downregulating the expression of Bax and cleaved caspase 3, as well as upregulating the expression of B-cell lymphoma 2 (Bcl-2), the Porelis dramatically inhibited 6-OHDA-induced apoptosis. Conclusion: The Porelis could be utilised to treat or prevent neurodegenerative diseases. It subsided oxidative stress and apoptosis in 6-OHDA-induced SHSY-5Y cells.
Keywords: Antioxidative enzymes; Apoptosis; Neurodegenerative disease; Neuroinflammation; Standardized extract